2022
DOI: 10.1084/jem.20211894
|View full text |Cite
|
Sign up to set email alerts
|

MPST sulfurtransferase maintains mitochondrial protein import and cellular bioenergetics to attenuate obesity

Abstract: Given the clinical, economic, and societal impact of obesity, unraveling the mechanisms of adipose tissue expansion remains of fundamental significance. We previously showed that white adipose tissue (WAT) levels of 3-mercaptopyruvate sulfurtransferase (MPST), a mitochondrial cysteine-catabolizing enzyme that yields pyruvate and sulfide species, are downregulated in obesity. Here, we report that Mpst deletion results in fat accumulation in mice fed a high-fat diet (HFD) through transcriptional and metabolic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…CSE has been previously reported to play a key role in the regulation of the adipogenesis, although with opposite effects as compared with 3-MST. Indeed, while CSE inhibition reduced lipid storage [ 10 , 27 ], 3-MST inhibition increased lipid accumulation as shown both in vivo model [ 28 ] and in vitro (Fig. 2D , E ).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…CSE has been previously reported to play a key role in the regulation of the adipogenesis, although with opposite effects as compared with 3-MST. Indeed, while CSE inhibition reduced lipid storage [ 10 , 27 ], 3-MST inhibition increased lipid accumulation as shown both in vivo model [ 28 ] and in vitro (Fig. 2D , E ).…”
Section: Resultsmentioning
confidence: 83%
“…6A ). Importantly, in a recently published study, increased adipocyte surface area was also demonstrated in vivo after 3-MST inhibition or silencing in C57Bl/6 J mice [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations